2017
DOI: 10.1039/c6re00224b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of catalyst injection conditions on the gas phase polymerization of propylene

Abstract: In the current work, gas phase propylene polymerizations were performed on ZN catalysts in a stopped flow reactor to understand the effect that the injection conditions (dry, as received, or wetted with a commercially available paraffinic mineral oil) have on initial temperature profiles, nascent polymer properties, and polymerization kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…It is worth recalling that during the production of sample A70‐13‐40‐8, precontacting procedure was avoided. It has been shown that samples which did not undergo this procedure presented smaller mesoparticles . Indeed, this seems to be the case when comparing the mesoparticles size of sample A70‐13‐40‐8 in Figure to the others.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…It is worth recalling that during the production of sample A70‐13‐40‐8, precontacting procedure was avoided. It has been shown that samples which did not undergo this procedure presented smaller mesoparticles . Indeed, this seems to be the case when comparing the mesoparticles size of sample A70‐13‐40‐8 in Figure to the others.…”
Section: Resultsmentioning
confidence: 80%
“…This can be done by changing the precatalyst (as shown by Smolná et al), or, if the same precatalyst is maintained, modifying its preparation and injection, as well as the phase in which the polymerization is carried out. The homopolymerization step can show different activities and lead to different morphologies depending on these factors, as shown in previous publications . In the current work, different precontact procedures between precatalyst, alkyl aluminium, and external lewis base were used to obtain different iPP morphologies, as shown by Cancelas et al Keeping constant copolymerization conditions and ethylene/propylene ratio, the influence of iPP morphology on the EPC distribution was studied.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations